Patho- and morphogenesis of microcirculation disturbances in toxic hepatitis in immature rats. - Rykalo, N. A. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Chronic exogenous intoxication leads to the development of typical pathological processes. In this case the structural and functional disturbanses of the liver frequently occur. Objective: to investigate the pathogenic and morphogenetic violations of blood and lymph circulation at chronic toxic hepatitis in immature rats. Methods. Experiment was conducted on white laboratory immature rats. The chronic toxic hepatitis was modelled by intragastric administration of 20% oil solution of CCl4 and 5% solution of ethanol during six weeks twice a week. Liver tissue was stained by hematoxylin and eosin and by Van Gieson for histological studies. Results. The liver is an important lymph producer in both normal and pathological conditions. At chronic toxic hepatitis in immature rats violation of lymph circulation leads to the dilation of lymph capillaries of the portal tracts and liver capsule, presence of anastomoses between superficial and deep lymphatic vessels, formation of new lymph vessels under the liver capsule, appearance of splits, lacunae, capillaries with a wide lumen, deformating the liver lobule. Connective tissue proliferation takes place on the background of lymphostasis. Сonclusion. The accumulation of fluid in the space of Disse can lead to capillarisation of sinusoids with formation of blood and lymphatic capillaries with the central direction of the fluid flow.